Granulomas associated with prolonged use of tracheostomy tube: Case report - Nakazato Nakamine, Teresa (2013)
The chronic carrying patient of tracheostomy can develop respiratory insufficiency caused by complications associated to the use of the tube. It is necessary to recognize the different causes to be able to determine the best handling of the tracheostomy complications. We present the case of a chronic carrying patient of tracheostomy by laryngeal stenosis, who after three years of tracheostomy develops respiratory insufficiency due to tracheal granulomas.